Antibacterial and antioxidant potentials, detection of host origin compounds, and metabolic profiling of endophytic Bacillus spp. isolated from Rauvolfia serpentina (L.) Benth. ex Kurz - Rusi Lata; Surendra Kumar Gond (Scientific Reports)
Abstract The research highlights the importance of exploring endophytic microbiomes of medicinal plants to uncover their potential for secondary metabolite production and their role in the biosynthesis of host-derived compounds. This study was aimed to isolate leaf endophytic bacteria of Rauvolfia serpentina, investigate their antibacterial, antioxidant potentials and detect host-origin compound reserpine using Reverse Phase High-Performance Liquid Chromatography (RPHPLC). Untargeted analysis via Ultra High-Performance Liquid Chromatography-High-Resolution Mass Spectrometry (UHPLC-HRMS/MS) was conducted for profiling main phytochemicals in the leaves and to explore potential bioactive compounds in bacterial extracts. Nine bacterial isolates were obtained from R. serpentina leaves. These isolates exhibited positive results in various biochemical tests including indole production, methyl red, Voges-Proskauer, citrate utilization, catalase and oxidase production, nitrate reduction, oxidative fermentation, and citrate reduction tests. Endophytic isolates RSLB3 and RSLB18 exhibited most potential antibacterial activity against tested human pathogenic bacteria and were identified as Bacillus sp. The extract of RSLB3 and RSLB18 also showed significant antioxidant activity compared to leaf extract. The total phenol content was similar in both these isolates while flavonoids content and DPPH scavenging activity was higher in isolate RSLB3. RPHPLC analysis confirmed the presence of reserpine in bacterial metabolites when compared to a standard reference. UHPLC-HRMS profiling unveiled a diverse range of host-derived compounds and reaction intermediates with known and unknown bioactive properties in leaf extract, RSLB3, and RSLB18. To our knowledge, this is the first study to achieve a comprehensive profiling.